Seasonal mortality patterns due to diseases of the circulatory system in Portugal - Almendra, Ricardo (2022)
Exposure to cold weather has negative consequences on human health. Studies have been showing that the seasonality of mortality has an evident peak during winter months in European countries. However, the highest increases in mortality are registered in countries with mild winters. According to several studies winter deaths seem to be associated with low socioeconomic conditions. The main aims of this study are to identify the trends of mortality due to diseases of the circulatory system and excess winter deaths in Portugal and to assess the geographical pattern of seasonal mortality. In the 20 years under analyses, mortality due to diseases of the circulatory system increased 38% during winter months when compared to the non-winter period. Important regional disparities were found, the Excess Winter Death index ranged from 21% to 48%, the central regions tend to have better results. Our results indicate that although circulatory mortality is significantly decreasing in Portugal, the vulnerability to seasonal cold weather remains as an important public health issue. These findings suggest that the exposure to cold weather is an important determinant of cardiovascular diseases that is still neglected in Portugal.